Computer based speed controller for DC motor using XS95 CPLD (Xilinx) / Syinorizra Nashriby Sharudin - Sharudin, Syinorizra Nashriby (2003)
This paper consists of developing a speed controller system for DC motors. The 3-phase half wave rectifier using Complex Programmable Logic Device or CPLD (XS95) using Xilinx software will be use to design the controller. To vary the speed of the DC Motor, the firing angle (u) of the thyristors should be varying by using external data controller (using 8-bit DIP switch). Thus, CPLD is use to control the thyristors, where it switch sequentially during positive cycle of the input voltage. This will vary the firing angles (u) such to control the output of 3-phase half wave rectifier. The DC voltage produced at the output can be maximum voltage (for high speed) or low voltage (for minimum speed) for the DC Motor. In order to make the controlling of the output of certain system via a rectifier easier, it is possible to control the input signal through it. Since the input signals are fed from the three-phase power supply, there are several interface circuit must be connected to merge the operational of rectifier. The digital software then, controls all the interface circuit where it is download into an external board for implementation called CPLD. When the complete circuit is operating, the input signal setting can be control by varying the firing angle u. Once it controlled, it will produced the output as expected. The observation can be made through the waveform shape where it is represented by mean voltage.